Disclosing the potential of eleganolone for Parkinson's disease therapeutics: Neuroprotective and anti-inflammatory activities. (June 2021) - Silva, Joana; Alves, Celso; Pinteus, Susete; Susano, Patrícia; Simões, Marco; Guedes, Miguel; Martins, Alice; Rehfeldt, Stephanie; Gaspar, Helena; Goettert, Márcia; Alfonso, Amparo; Pedrosa, Rui
Abstract: The treatment of Parkinson´s disease (PD) has benefited from significant advances resulting from the increasing research efforts focused on new therapeutics. However, the current treatments for PD are mostly symptomatic, alleviating disease symptoms without reversing or retarding disease progression. Thus, it is critical to find new molecules that can result in more effective treatments. Within this framework, this study aims to evaluate the neuroprotective and anti-inflammatory effects of three compounds (eleganolone, eleganonal and fucosterol) isolated from the brown seaweed Bifurcaria bifurcata. In vitro neuroprotective effects were evaluated on a PD cellular model induced by the neurotoxin 6-hydroxydopamine (6-OHDA) on SH-SY5Y human cells, while lipopolysaccharide (LPS) − stimulated RAW 264.7 macrophages were used to evaluate the anti-inflammatory potential. Additionally, the underlying mechanisms of action were also investigated. Compounds were isolated by preparative chromatographic methods and their structural elucidation attained by NMR spectroscopy. Among the tested compounds, eleganolone (0.1–1 µM; 24 h) reverted the neurotoxicity induced by 6-OHDA in about 20%. The neuroprotective effects were mediated by mitochondrial protection, reduction of oxidative stress, inflammation and apoptosis, and inhibition of NF-kB pathway. The results suggest that eleganolone may provide advantages in the treatment of neurodegenerative conditions and, therefore, should be considered for future preclinical studies. Graphical Abstract: ga1